2008
DOI: 10.1227/01.neu.0000313120.81565.d7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Stereotactic Radiosurgery for Intracranial Hemangioblastomas

Abstract: A new classification of spinal deformity is proposed that provides a structure for defining deformity of all patient ages and spinal abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(33 citation statements)
references
References 85 publications
0
30
2
1
Order By: Relevance
“…Some previous reports noted worse progression-free survival for sporadic hemangioblastomas than for VHL-associated hemangioblastomas [12, 15] However, our study and that of Matsunaga et al did not observe such a difference [11]. …”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Some previous reports noted worse progression-free survival for sporadic hemangioblastomas than for VHL-associated hemangioblastomas [12, 15] However, our study and that of Matsunaga et al did not observe such a difference [11]. …”
Section: Discussioncontrasting
confidence: 94%
“…Data from the literature have revealed that larger tumor volume is significantly associated with poorer progression-free survival after GammaKnife (GK) [7, 12], while another study only observed a trend in this direction [15]. In contrast, neither our study nor a report from Matsunaga et al detected a correlation in the size of the tumor with growth control after SRS [11].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Thus, one explanation for the differences between the results of the above studies and ours could be that in a young cohort, changes of the spinal posture due to athletic training are muscular rather than structural or degenerative changes, as seen in older cohorts. It is also important to recognize that in different paediatric groups, there are wide variations in the sagittal alignment of the spine that can confound comparison (Kuntz et al, 2008).…”
mentioning
confidence: 99%
“…These reports have presented excellent control rates within short-term follow-up, with some reports of control rates exceeding 90% at 2 and 5 years. 7,8,17,22,25,28 Recent long-term prospective evaluation of radiosurgery for the treatment of cerebellar and brainstem hemangioblastomas in VHL disease revealed favorable control rates at 2 and 5 years but declining efficacy in tumor control over time, reaching 61% and 51% at 10 and 15 years, respectively. 2 Furthermore, exacerbation of neurological deficits as a result of increased peritumoral edema after radiosurgery may limit the use of this modality in symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%